2008
DOI: 10.1177/147323000803600619
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Efficacy of the Bio-Absorbable Oxidized Regenerated Cellulose for Prevention of Post-Operative Pericardial Adhesion in the Rabbit Model

Abstract: Pericardial adhesions complicate re-operative cardiac surgery and several attempts have been made to reduce adhesion formation. The efficacy of bio-absorbable oxidized regenerated cellulose in preventing post-operative pericardial adhesions was evaluated in the present study. Forty New Zealand white rabbits were divided into four groups of 10. In all rabbits an area of pericardium (2 x 2 cm) was excised. The wound was left open in groups 1 and 2 but replaced with bio-absorbable oxidized regenerated cellulose i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Nevertheless, while recurrence rates of around 10 % were seen in the PGA/TC cases, no postoperative recurrence was observed in the ROCM series. A recent animal study revealed that covering tissue with ROCM prevents a long-term foreign body reaction and the development of adhesions at the surgical site, and also increases mesothelium-like cell proliferation [5]. These results suggest that ROCM may prevent pleural adhesions and strengthen the visceral pleura by increasing its thickness [6].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, while recurrence rates of around 10 % were seen in the PGA/TC cases, no postoperative recurrence was observed in the ROCM series. A recent animal study revealed that covering tissue with ROCM prevents a long-term foreign body reaction and the development of adhesions at the surgical site, and also increases mesothelium-like cell proliferation [5]. These results suggest that ROCM may prevent pleural adhesions and strengthen the visceral pleura by increasing its thickness [6].…”
Section: Discussionmentioning
confidence: 99%
“…reported that ORC's efficacy in a postoperative pericardial adhesion model of New Zealand white rabbit. [ 121 ] Various other studies also suggested that Interceed helps prevent adhesion in an intraabdominal wall and uterus abrasion rabbit model compared with the control group, while it showed less efficacy in adhesion prevention than the HA/sodium alginate‐based microparticle antiadhesion agents. [ 122 ] In addition to a number of animal studies that suggested that the important role of Interceed [ 123,124 ] and several clinical trials further proved adhesion prevention efficacy.…”
Section: Biomaterials To Fabricate Antiadhesion Barriersmentioning
confidence: 99%
“…Interceed has been studied in animal models in combination with heparin and has been shown to significantly reduce adhesion formation in rabbit uterine horn [240,241] and pericardium [242]. Similarly, other human trials generally find that Interceed reduces the severity, extent, and/or incidence of pelvic adhesions [243][244][245][246][247][248].…”
Section: Cellulose Based Barriersmentioning
confidence: 99%